Evaluating Frugivore-fruit Interactions Using Avian Eye Modelling - Fadzly, Nik (Penerbit Universiti Sains Malaysia, 2013)
Fruit phenotypes are often hypothesised to be affected by selection by frugivores. Here, we tested two hypotheses concerning frugivore-fruit interactions from the perspective of fruit colours. We measured the spectral properties of 26 fruits and the associated leaves of plants from 2 islands in New Zealand. Visual observations were also performed to record the birds that fed on the fruits. First, we tested the fruit-foliage hypothesis, where fruit colours are assumed to be evolutionarily constrained by their own leaf colour to maximise colour contrast and fruit conspicuousness. We ran a null model analysis comparing fruit colour contrast using an avian eye model. Second, we tested the frugivore specificity hypothesis, where specific fruit colours are thought to be connected with a specific bird frugivore. We performed a regression on the number of bird visits against the fruit colour in tetrahedral colour space based on an avian eye calculation using Mantel’s test. The results show that fruit colours are not constrained by their own leaf colours. There is also no relationship or pattern suggesting a link between a specific fruit colour and specific bird visitors. We suggest that although fruit colour is one of the most highly discussed components, it is not the most important single deciding factor in frugivore fruit selection.